AKSELERASI PROGRAM EDUKASI KEUANGAN MELALUI KOLABORASI BANK INDONESIA, LEMBAGA KEUANGAN, DAN PERGURUAN TINGGI - I Wayan Nuka Lantara; Ni Ketut Rai Kartini (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2015)
This study aims to investigate the possibility of acceleration of financial education programs in Indonesia, through the collaboration of the three main parties, namely: (1) the regulator (Central Bank/Financial Services Authority); (2) the practitioner (financial institutions); and (3) the academia (universities). The study employed a qualitative approach to assess the opinions of the stakeholders in the Gadjah Mada University and related financial practitioners regarding accelerated implementation of financial education programs in Indonesia, which involved interviews with 24 informants who were considered to have knowledge about the financial education program in Indonesia. The study concluded that the respondents showed a positive perception on the importance and benefits of financial education programs in Indonesia. Other findings depicted that financial education programs need to be directed at the entire community with a wider coverage range. To expedite the process, a solid collaboration needs to be made between the three main parties: (1) Central Bank/ Financial Services Authority as regulator; (2) financial institutions (practitioners and providers of financial products and services); and (3) academia (universities). In terms of the implementation of the proposed program, the collaboration of all three parties need to be directed to the selected students who will firstly be prepared to be a financial educator (by giving knowledge, education and mentoring). Selected and well-trained students are expected to be effective educator who has energy resource availability in large quantities and a more mobile and larger coverage to accelerate financial education program in Indonesia.